Analysis of Codon Usage of Speech Gene FoxP2 among Animals - Tarikul Huda Mazumder; Ali M. Alqahtani; Taha Alqahtani; Talha Bin Emran; Afaf A. Aldahish; Arif Uddin (Biology, 2021)
The protein-coding gene FoxP2 (fork head box protein P2) plays a major role in communication and evolutionary changes. The present study carried out a comprehensive codon usage bias analysis in the FoxP2 gene among a diverse group of animals including fishes, birds, reptiles, and mammals. We observed that in the genome of fishes for the FoxP2 gene, codons ending with C or G were most frequently used, while in birds, reptiles, and mammals, codons ending with T or A were most frequently used. A higher ENC value was observed for the FoxP2 gene indicating a lower CUB. Parity role two-bias plots suggested that apart from mutation pressure, other factors such as natural selection might have influenced the CUB. The frequency distribution of the ENC observed and ENC expected ratio revealed that mutation pressure plays a key role in the patterns of codon usage of FoxP2. Besides, correspondence analysis exposed the composition of the nucleobase under mutation bias affects the codon usage of the FoxP2 gene. However, neutrality plots revealed the major role of natural selection over mutation pressure in the CUB of FoxP2. In addition, the codon usage patterns for FoxP2 among the selected genomes suggested that nature has favored nearly all the synonymous codons for encoding the corresponding amino acid. The uniform usage of 12 synonymous codons for FoxP2 was observed among the species of birds. The amino acid usage frequency for FoxP2 revealed that the amino acids Leucine, Glutamine, and Serine were predominant over other amino acids among all the species of fishes, birds, reptiles, and mammals.